Robot-assisted staged bilateral reno-lymphatic disconnection for massive idiopathic chyluria: A case report - Sonia Costantino; Francesca Montanaro; Alberto Bianchi; Greta Pettenuzzo; Riccardo Bertolo; Maria Angela Cerruto; Alessandro Veccia; Alessandro Antonelli (Urology Case Reports, 2024)
Chyluria, an abnormal lymphatic disorder, results in excessive abdominal lymph drainage into the urinary system, causing protein loss, nutritional deficiencies, and immune issues. Mainly linked to parasitic infections in developed countries, non-parasitic causes like trauma or tumors are rare. Typically appearing in adults with bilateral involvement, management options include conservative or surgical approaches. We present the case of a 13-year-old with congenital chyluria, treated with robot-assisted staged reno-lymphatic disconnection after failed interventional radiology. Bilateral scleroangiography followed, leading to persistently milky urine for a month. Finally, urine clarity improved, correlating with better urinalysis, emphasizing the need for a comprehensive, multi-disciplinary approach.